Three-Dimensional in vitro Models of Healthy and Tumor Brain Microvasculature for Drug and Toxicity Screening - Piantino, Marie; Figarol, Agathe; Matsusaki, Michiya (Frontiers in Toxicology, 2021)
Tissue vascularization is essential for its oxygenation and the homogenous diffusion of nutrients. Cutting-edge studies are focusing on the vascularization of three-dimensional (3D) in vitro models of human tissues. The reproduction of the brain vasculature is particularly challenging as numerous cell types are involved. Moreover, the blood-brain barrier, which acts as a selective filter between the vascular system and the brain, is a complex structure to replicate. Nevertheless, tremendous advances have been made in recent years, and several works have proposed promising 3D in vitro models of the brain microvasculature. They incorporate cell co-cultures organized in 3D scaffolds, often consisting of components of the native extracellular matrix (ECM), to obtain a micro-environment similar to the in vivo physiological state. These models are particularly useful for studying assaults on the healthy brain vasculature. They provide insights into the molecular and cellular events involved in the pathological evolutions of this vasculature, such as those supporting the appearance of brain cancers. Glioblastoma multiform (GBM) is the most common form of brain cancer and one of the most vascularized solid tumors. It is characterized by a high aggressiveness and therapy resistance. Current conventional therapies are unable to prevent the high risk of recurrence of the disease. Most of the new drug candidates fail to pass clinical trials, despite the promising results shown in vitro. The usual in vitro models are unable to efficiently reproduce the specific features of GBM tumors. The high heterogeneity of the brain vasculature network resulting from the constant remodeling of the ECM by glioma cells is a challenge that tissue engineering is currently taking up. In this review paper, after summarizing the advances in 3D in vitro brain vasculature models, we focus on the latest achievements in vascularized GBM modeling, and the potential applications for both healthy and pathological models as platforms for drug screening and toxicological assays. Particular attention will be paid to discuss the relevance of these models in terms of cell-cell, cell-ECM interactions, vascularization and permeability properties, factors crucial for improving in vitro testing accuracy.